2009
DOI: 10.1186/1471-2148-9-294
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of the common vampire bat (Desmodus rotundus): Marked population structure, Neotropical Pleistocene vicariance and incongruence between nuclear and mtDNA markers

Abstract: BackgroundThe common vampire bat Desmodus rotundus is an excellent model organism for studying ecological vicariance in the Neotropics due to its broad geographic range and its preference for forested areas as roosting sites. With the objective of testing for Pleistocene ecological vicariance, we sequenced a mitocondrial DNA (mtDNA) marker and two nuclear markers (RAG2 and DRB) to try to understand how Pleistocene glaciations affected the distribution of intraspecific lineages in this bat.ResultsFive reciproca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
89
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(100 citation statements)
references
References 76 publications
(72 reference statements)
9
89
0
2
Order By: Relevance
“…The ubiquity of sex-biased dispersal in animals suggests sex-biased pathogen spread could widely influence the distribution and invasion dynamics of emerging diseases. Prior population genetic studies concluded that the low vagility and small home range sizes of vampire bats generate high genetic differentiation among populations (12,13). However, genetic lineages of VBRV are geographically widespread, implying that the virus overcomes the genetic isolation of its host through a currently unidentified dispersal mechanism (14,15).…”
Section: Significancementioning
confidence: 99%
“…The ubiquity of sex-biased dispersal in animals suggests sex-biased pathogen spread could widely influence the distribution and invasion dynamics of emerging diseases. Prior population genetic studies concluded that the low vagility and small home range sizes of vampire bats generate high genetic differentiation among populations (12,13). However, genetic lineages of VBRV are geographically widespread, implying that the virus overcomes the genetic isolation of its host through a currently unidentified dispersal mechanism (14,15).…”
Section: Significancementioning
confidence: 99%
“…vampire bats from different geographic mtDNA clades with the biogeographic pattern revealing strong population structure suggesting the possibility of cryptic species (Martins, Ditchfield, Meyer, & Morgante, 2007). Martins, Templeton, Pavan, Kohlbach, and Morgante (2009), examined vampire bats samples from Central America and Brazil by using mitochondrial and nuclear markers. Their results revealed geographical structure with a historical scenario with mtDNA but no phylogeographic structure with nuclear markers and suggested that these contrasting patterns are compatible with complete isolation in Pleistocene refuges.…”
mentioning
confidence: 99%
“…cruzii complex is compatible with a historical scenario of populations isolated during the Pleistocene ecological changes (Carnaval et al, 2009). The subdivision of the Brazilian Atlantic Forest has been recognized as a cause of endemicity, for example, in bats (Martins et al, 2009) and pit vipers (Grazziotin et al, 2006) and climatic changes have been proposed to explain the differentiation among many forestobligate species (Carnaval et al, 2009;Marroig et al, 2004;Pedro et al, 2008).…”
Section: Resultsmentioning
confidence: 75%